Transcultural and Imagological Figures: Disenchantment, Allophilia, and Belonging in Enrique Vila-Matas and Antonio Tabucchi - Simões, Maria João (2017)
In some contemporary literary works, the presence of the ‘other’ and the representation of the ‘foreigner’ emphasize the problematic ways by which human beings relate to foreign people, revealing how those issues are pressing concerns in modern society. This study questions how the shift in the way we perceive identity and belonging are depicted in Enrique Vila-Matas and Antonio Tabucchi’s fictions. Both authors aesthetically represent episodes and situations where characters’ relation to space is problematic, showing how the idea of belonging can be related not only to a specific country or a special space, but also to a desired space. Furthermore, based on the pregnancy of the notion of ‘dwelling’ theorized by Emmanuel Levinas, this study analyses how characters and narrators aesthetically represent the complexity of belonging and examines some of the transnational transfers and multicultural connexions displayed by both autors, mainly in Never Any End to Paris and It’s Getting Later All the Time.